2013
DOI: 10.4250/jcu.2013.21.2.58
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Dose versus High Dose Statin Therapy on the Changes of Endothelial Function and Carotid Intima-Media Thickness in Patients with Variant Angina

Abstract: BackgroundTo compare the effects of low dose and high dose of statin treatment on endothelial function and carotid intima-media thickness (IMT) in patients with variant angina (VAP).MethodsA total of 70 patients with VAP were divided into two groups; atorvastatin 10 mg treatment group (group I: n = 35, 54.2 ± 12.5 years) versus atorvastatin 40 mg treatment group (group II: n = 35, 52.6 ± 9.8 years). Flow mediated vasodilation (FMD) of the brachial artery and IMT of the carotid artery were compared between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Apart from antihypertensive drugs, statins have been shown to reduce cIMT in patients with familial hypercholesterolaemia [255] and dyslipidaemia in general [276]. Nevertheless, some studies failed to show a decrease in cIMT after a 6-month treatment with statins [257,277]. Whether a more prolonged statin treatment might lead to a reduction in cIMT is not clear.…”
Section: Pharmacological Modification Of Vascular Biomarkers and CV Riskmentioning
confidence: 99%
“…Apart from antihypertensive drugs, statins have been shown to reduce cIMT in patients with familial hypercholesterolaemia [255] and dyslipidaemia in general [276]. Nevertheless, some studies failed to show a decrease in cIMT after a 6-month treatment with statins [257,277]. Whether a more prolonged statin treatment might lead to a reduction in cIMT is not clear.…”
Section: Pharmacological Modification Of Vascular Biomarkers and CV Riskmentioning
confidence: 99%
“…Finally, the numbers of the study subjects are relatively small to detect the difference of vascular function between atorvastatin 40 mg and atorvastatin 10 mg. In the study of Kim et al,11) it seems to be more increase of flow mediated dilation in atorvastatin 40 mg group (7.9 ± 2.7% to 9.5 ± 2.8%) than those in atorvastatin 10 mg group (7.7 ± 2.5% to 8.9 ± 2.2%). But, these results were statistically insignificant due to under-powered sample size.…”
mentioning
confidence: 81%
“…Recent clinical evidences also showed that combined therapy with a statin and a calcium channel blocker may attenuate coronary vasoconstriction as well as systemic endothelial dysfunction in patients with VAP 9)10). In this issue of Journal of Cardiovascular Ultrasound , Kim et al11) also support the evidence that the use of atorvastatin, regardless of dosage, could improve systemic endothelial function as measured by flow mediated dilation of the brachial artery in patients with VAP. Collectively, statin might modify the underlying pathogenesis of coronary artery spasm and be a novel therapeutic drug for coronary artery spasm in patients with VAP.…”
mentioning
confidence: 84%
See 2 more Smart Citations